Ризики у рекламному бізнесі - Невлюдов, І. Ш.; Рожнова, Т. Г.; Солодовник, Г. В. (ХНУРЭ, 2014)
The instability of the economic processes of the transformation period requires permanent monitoring of risks. The article is devoted to the issues of qualitative and quantitative risk analysis at the enterprises of average and small business.
Keywords: ризики; рекламний бізнес